Yoghurt making training to build women’s resilience in developing local economy and healthy lifestyle - Eko Nursanty; Honorata Ratnawati Dwi Putranti; Ery Fatarina Purwaningtyas (Universitas Muhammadiyah Malang, 2022)
Lifestyle modifications are becoming increasingly important, especially following the epidemic era. Healthy living is a continual lifestyle that aids the attempt to transform a healthy culture and the production of healthy cells. A healthy lifestyle is one that consider all facets of a person's health. Not only about food but also about exercise and lifestyle practices. Health is vital to all our actions. One of the important things in supporting health can be done with healthy food intake. Making homemade yogurt, changing other foods, and changing one's lifestyle are all part of this activity. Thus, this activity aims to train partners in yogurt making to build women's resilience in developing local economies and healthy lifestyles. Activities are hybrid, with some participants and resource personnel working online and others offline at the activity site. The method of activities is carried out using lectures, discussions and hands-on practice which is carried out in a hybrid between online and offline. Some participants and resource persons carry out activities online and partly offline at the activity location. This activity is women's independence to build a home industry producing yogurt and other nutritious foods has increased, as has the production of processed yogurt. It is anticipated that the independence of these women will encourage the self-assurance necessary to construct a healthy family and environment, making their residence a place of business and a healthy gastronomic destination at home.